Pengembangan Media “Papan Tempel Data” Pada Pembelajaran Matematika Materi Diagram Kelas 1 SDN 03 Jembatan Lima - Syahwa, Artha Mahira; Ritonga, Rudi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to develop a learning medium called the Data Pin Board to enhance students’ understanding of diagrams in mathematics for first-grade elementary students. The research employed the Research and Development (R&D) method using the Borg and Gall model, which consists of ten stages of development. The medium was designed as a magnetic board with movable pins and integrated QR codes that link to instructional videos and educational games. Validation results showed high feasibility, with scores of 90% from media experts and 94% from content experts. Field testing involving 32 students showed an increase in average scores from 62.8 to 81.5, with an N-Gain score of 0.56 (moderate category), and a very positive student response rate of 91%. This study offers novelty by integrating concrete and digital tools into an interactive medium tailored to the characteristics of young learners. These results demonstrate that the Papan Tempel Data is a feasible and effective instructional tool that enhances conceptual understanding of diagrams through an engaging, interactive, and concrete learning experience.